Game-based learning and simulations to enhance FET History teaching practices - Lachman, Sarah Jersuaha (University of the Witwatersrand, Johannesburg, 2024)
This study investigates the integration of game-based learning and simulations for teaching practices of Further Education and Training (FET) History educators. In traditional pedagogical approaches, History instruction often lacks the engagement necessary to captivate modern learners, who increasingly seek interactive and stimulating educational experiences. Despite the prevalence of digital technologies in educational settings, History teachers have been slow to adopt these tools to enhance their teaching methods. This research addresses this gap by advocating for the incorporation of digital game-based learning and simulation-based learning to create more engaging and effective History lessons. Drawing on literature that underscores the benefits of technology enhanced pedagogies and South African participants experiences in the classroom, this study explores how educators can leverage digital games and simulations to align their teaching with the technological preferences of contemporary learners, finding the most favorable game- based applications and simulations to use. Existing research indicates that game-based learning and simulations not only enhance student engagement but also promote better retention of historical information. By employing a blended learning approach, which integrates digital tools into traditional instruction, educators can effectively transition away from outdated pedagogical methods and provide students with dynamic and immersive learning experiences. The research aims to empower educators to transform their teaching practices, making History lessons more stimulating and relevant to the digital-native generation. Through this exploration, educators are encouraged to embrace technology-driven teaching methods that both involve and interest learners while reinforcing essential historical concepts.
A research report submitted in fulfillment of the requirements for a Master of Education, In the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Game-based learning; simulation based learning; Virtual Reality; Kahoot!; MineCraft Education; SDG-4: Quality education